Food Market Development Socio-Economic Forecast Mechanism Study Methodology - Zukhra, Abdurakhmanova (American Journal of Economics and Business Management, 2025)
Population active growth, resources for of struggle increase, food and drink water shortage of the problem exacerbation with described society development current Optimal nutrition during the phase market formation and management effective from the means use In Uzbekistan food safety enough at the level provide priority is a task. So just do it forecast of the subject psycho-e emotional to experience based intuitive, economical and of nature development laws to know based scientific forecast These forecasts are available, the future prophecy as in society economic to problems end to give help gives. The essence of forecasting is reduced to the process of developing forecasts based on the analysis of trends and patterns of development of the object. It should be noted that in practice, the use of any forecasting method to justify management decisions usually leads to a decrease in the accuracy, probability and reliability of forecast results. Therefore, in order to ensure the adoption of high-quality management decisions, it is necessary to select the most optimal forecasting methods for the object under study and correctly combine them.